Flows and frictions in Trans-Himalayan spaces: histories of networking and border crossing - Cederlöf, Gunnel; Schendel, Willem van (Asian Borderlands, 2022)
Flows and Frictions in Trans-Himalayan Spaces traces movements and connections in a region known for its formidable obstacles to mobility. Eight original essays and a conceptual introduction engage with questions of networks and interconnection between people across a bordered landscape. Mobility among the extremely varied ecologies of south-western China, Myanmar and north-eastern India, with their rugged terrain, high mountains, monsoon-fed rivers and marshy lowlands, is certainly subject to friction. But today, harsh political realities have created hard borders and fractured this trans-Himalayan terrain. However, the closely researched chapters in this book demonstrate that these borders have not prevented an abundance of movements, connections and flows. Mobility has always coexisted with friction here, but this coexistence has been unsettled, giving this space its historical shape and its contemporary dynamism. Introducing the concept of the 'corridor' as an analytical framework, this collection investigates mobility and flows in this unique socio-political landscape